THE EFFECT OF WORK STRESS, TRAINING, AND COMPETENCE ON PERFORMANCE OF KARIMUN POLICE PERSONNEL, RIAU ISLANDS REGIONAL POLICE, WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Ulfa; Bambang Satriawan; Nolla Puspita Dewi (CV. RADJA PUBLIKA, 2024)
Human resources are the driving force of an organization. Without human resources, the organization will not be able to carry out the process of growing and moving. Human resources are so important for the survival of the organization that there must be special treatment carried out by managers and stakeholders of the organization to be able to carry out good empowerment so that human resources in the organization can provide optimal performance for the survival of the organization. Employee performance is the work results in terms of quality and quantity achieved by an employee in carrying out his/her civil servant duties in accordance with the responsibilities given to him/her. Therefore, it can be said that human resource performance is the achievement or work results in terms of quality and quantity achieved by employees in a certain period. research variables are attributes or characteristics or aspects of people or objects that have certain variations that are determined by researchers to be studied and conclusions drawn. Meanwhile, according to Kerlinger. variables are characteristics that can have various values. Furthermore, it is stated that variables are symbols that have values ​​in the form of numbers. So variables are symptoms or characteristics of an object that have variations or values ​​that are different from other objects that are the focus of researchers to observe.